(3GdeSDhdjI GdWHjI Yf aYd GdZjQ (B: s (3OQGSI ebGQfI (B/ s - (3fGUQ RcQjG MSjf CHhQeGfs; (3eMeO SGei YHOGdUGObs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2019)
(3h deG ncGnf ddJbOe GdgGFd paj eLGd GdpqWqH GfYcGSGJg Ydi eSDhdnqjI GdeSJTajGJ h GdnCpWnqHGA hGdLnqQGMjf(B: (3aJRGjOJ GdMGdGJ GnqdpJj JKhQ ajgG eSDhdjGJge(B: (3h HOCJ gPg GdXGgQI eY ChGFd GdbQf GdYTQjf(B: (3h RGO eYOdgG paj GdCQHYjf SfI GdeGVjI(B: (3h JRGjO YOO GdbVGjG GdehLgI VOge(B. (3h JfgV YOI CSHGH dJaSjQ ngnPG GdJRGjO paj eLGd GdeSDhdnqjI GdpqWpqHnqjI(B: (3aHYVgG jQLY pEndi GdJWhQ GdWpqHqj PGJg(B: (3h GdHYV GdBNQ jQLY pEndi RjGOI OQLI GdhYj GdGLJeGYj(B. (3hgnPG GdJbOe GdgGFd paj af GdpYndGL h GdLQGMI OaY GdfGS pEndi GdMQU Ydi UMJge h SdGeJge(B: (3aaj eLGd GdJWhQ GdWpqHqj GNoJQYJ CLgRI h hSGFd afjI HGdZI GdJYbjO(B: (3h CJjM ddnCpWnqHGA GSJNOGegG(B: (3h GfYcS nPpdnc paj UhQI JbdU OhQ GdnqWpHjH GdaQO paj MjGI GdnepQjV djMd eMdg GdcGOQ GdpqWpqHj(B: (3abO JRGjOJ MGdGJ GdeSDhdnqjI GdpqWpqHnqjI(B: (3EP de JYO JbJUQ GdYedjGJ GdLQGMjI Ydi GdLnqQGM hMOg(B: (3Hd jTJQc eYg WHjH GdJNOjQ(B: (3h WGbe ef GdeSGYOjf(B: (3h oJLnQi GdYedjI OGNd CQhbI GdoeSnJrTai GdYGe Ch GdNGU(B: (3h oJSJYed COhjI h eYOGJ h BdGJ(B: (3hcd ngnPG jJWdH JMOjkOG deSDhdnqjI gDdGA GdCWQGa(B: (3EP Jbhe QhGHW eTJQcI ajeG Hjfge(B: (3h JJOGNd egGe cmqd efge(B. (3Gf GdeSDhdnqjI GdpqWpqHnqjI HhLg YGe eSDhdnqjI nYrbpOnqjI(B: (3h nPpdnc dGSJbQGQ CMcGe GdbVGA (B- (3Ydi QCSg bVGA GdnqfrbV (B- (3Ydi Jcjja GdnYdGbI Hjf GdnqWpHjH h eQjVg nYndGbI nYrbpOnqjI bhGegG GdYbO GdpqWpqHj(B: (3GdCeQ GnqdpPi LYdfG fJUOi deSCdI GdeSDhdnqjI Yf aYd GdnZrjQ pai GdfWGb GdnYrbpOqi(B: (3EP jUHM GdnepOjf eSDhkdG YbOkqjG Yf aYd ef GSJYGf Hge ai JfajP LRA ef GdJRGeg GdnYrbpOi JLGg GdOGFf(B: (3ceG JTcd GdeSDhdnqjI GdeOfnqjI YUkHG QFjSkqjG paj GdnbGofhf GdeOfjs
(3jTJed Ydi edMb(B: (3UaMI (B399-408.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2019.s
(3HHdjhLQGajG(B: (3UaMGJ (B362-388.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdeSDdjI GdWHjIs; (3GdeSDdjI Yf Yed GdZjQs; (3GdeSDhdjI GdYbOjIs; (3GdeSGYOjfs; (3GdeSFhdjI GdWHjIs; (3GdeSDhdjI GdWHjI Yf aYd GdZjQ aj GdGWGQ GdYbOis; (3fWGb JWHjb eSDhdjI GdWHjH GdYbOjI Yf aYd GdZjQs; (3TQhW bjGe eSDhdjI GdWHjH GdYbOjI Yf aYd GdZjQs; (3GdCSGS GdbGfhfj deSDhdjI GdWHjH GdYbOjI Yf aYd GdZjQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQI s -- (3GdbGfhf GdeOfjs